High-Pitch Low-Dose Whole-Body Computed Tomography for the Assessment of Ventriculoperitoneal Shunts in a Pediatric Patient Model: An Experimental Ex Vivo Study in Rabbits. Issue 12 (December 2015) - Othman, Ahmed E.; Afat, Saif; Hamou, Hussam A.; Pjontek, Rastislav; Tsiflikas, Ilias; Nikoubashman, Omid; Brockmann, Marc A.; Nikolaou, Konstantin; Clusmann, Hans; Wiesmann, Martin
Abstract : Objective: The aim of this study was to assess the diagnostic value of whole-body low-dose (LD) computed tomography (CT) for the detection of ventriculoperitoneal (VP) shunt complications in pediatric patients compared with radiographic shunt series (SS) in an ex vivo rabbit animal model. Methods: In the first step, 2 optimized LD-CT imaging protocols, with high pitch (pitch, 3.2), low tube voltages (70 kVp and 80 kVp), and using both filtered back projection and iterative reconstruction, were assessed on a 16-cm solid polymethylmethacrylate phantom regarding signal-to-noise ratio and radiation dose. Taking both radiation dose and signal-to-noise ratio into account, the LD-CT protocol (80 kVp; 4 mA; pitch, 3.2) was identified as most appropriate and therefore applied in this study. After identification of appropriate LD-CT protocol, 12 VP shunts were implanted in 6 rabbit cadavers (mean weight, 5.1 kg). Twenty-four mechanical complications (extracranial and extraperitoneal malpositioning, breakages, and disconnections) were induced in half of the VP shunts. Low-dose CT and conventional SS were acquired in standard fashion. Dose-area products (DAPs) for SS and LD-CT were collected; effective radiation doses for both SS and LD-CT were estimated using CT-Expo (v. 2.3.1.) and age-specific effective dose (ED) estimates. Qualitative scoring of diagnostic confidence on a 5-point Likert scale (1, very low diagnostic confidence; 5, excellent diagnostic confidence) and blinded readings of both SS and LD-CTs were performed. Results: Among the 24 VP shunt complications, LD-CT yielded excellent sensitivity and specificity for the detection of VP shunt complications (sensitivity, 0.98; specificity, 1; 95% confidence interval, 0.92-1) with excellent interobserver agreement (κ = 0.90). Shunt series yielded good sensitivity and specificity (sensitivity, 0.75; specificity, 1; 95% confidence interval, 0.58–0.92) with moderate interobserver agreement (κ = 0.56). No false-positive findings were registered. Compared with SS, LD-CT yielded significantly lower ED and DAPs (ED, 0.039 vs 0.062 mSv; DAP, 20.5 vs 26.3; P < 0.05). Conclusions: In this experimental ex vivo pediatric patient model, LD-CT yields excellent sensitivity for the detection of VP shunt complications at higher diagnostic confidence and lower radiation exposure compared with SS.